ANALISIS PENGGUNAAN TEKNOLOGI DALAM PROSES LATIHAN DAN PENINGKATAN PERFORMA ATLET TENIS MEJA - Damanik, Putra Tulus (Hanoman Journal: Physical Education and Sport, 2024)
In recent years, technology has developed rapidly and has begun to be applied in various fields, including sports. The use of technology in table tennis can help athletes improve their performance. Modern table tennis athletes face increasingly complex challenges in an effort to improve their performance on the court. In an effort to achieve optimal performance, technology has become an unavoidable key factor. The use of technology in the training process has become a major focus for coaches and athletes to achieve competitive advantage. This research aims to identify the use of technology in the training process and performance of table tennis athletes. The research method used is a qualitative descriptive method through literature study sourced from journals, scientific articles, books and other relevant sources. The results of this research show that there are various technologies commonly used in table tennis, such as ball robots, video analysis software, and performance sensors. The use of technology in the sport of table tennis provides a number of significant benefits for athletes and coaches. Technology enables the use of more sophisticated and precise equipment, such as rafts specifically designed to improve ball control, speed and effect, provides access to in-depth data and analysis of athlete performance, and enables realistic and interactive training simulations.